Tea Tree Oil Effect on Dimensional Change and Detail Reproduction of Addition Silicon Impression Material - Samir Samier Hammed; Aseel Mohammed Al-Khafaji (University Library System, University of Pittsburgh, 2024)
Objective: Impression materials are thought to be the one of the primary sources of cross infection between patients and dentists. However, it was discovered that disinfection of the impression is not conducted routinely in ordinary dental treatment. Disinfection of addition silicon impression, whether by immersion or spray should not produce dimensional or detail errors. The purpose of this study was to examine the immersion of addition silicon impression material in tea tree oil and its influence on dimensional stability and detail reproduction of the addition silicon imprint material. Materials and Methods: This study employed a total of 120 heavy- and light-body addition silicon impression material specimens. The specimens were randomly sorted and immersed into six groups. These test groups where four concentrations of TTO (0.25%, 0.5%, 0.75%, and 1%), and the other two groups were distilled water (negative control) and 2% glutaraldehyde (positive control). All specimens were immersed for 10 minutes in the testing solutions. Each of the six groups had 20 specimens separated into two subgroups. Results: There were no statistically significant differences in linear dimensional changes and detail reproduction among all test groups. Conclusion: The addition silicon impression material may be safely submerged in TTO for 10 minutes to disinfect it without impairing its dimensional correctness or detail replication of the impression.